Assessing biosimilar education needs among oncology pharmacy practitioners worldwide: An ISOPP membership survey. (April 2020) - Chan, Alexandre; Patel, Himanshu; Siderov, Jim; Bubalo, Joseph; Foreman, Emma
Background: The International Society of Oncology Pharmacy Practitioners (ISOPP) Biosimilar Task Force was charged to develop educational resources to address the learning needs related to biosimilars use of oncology pharmacy practitioners. To facilitate the process, the task force conducted a survey in order to identify unmet education needs as well as barriers for obtaining biosimilar education among oncology pharmacy practitioners. Methods: A cross sectional survey was conducted between 10 December 2018 and 18 February 2019. Members of International Society of Oncology Pharmacy Practitioners and national oncology pharmacy groups were invited to complete the survey. The survey contained 22 items and consisted of four sections. Descriptive statistics were utilized to analyze the survey results. Results: A total of 363 International Society of Oncology Pharmacy Practitioners members were surveyed, with 75 members providing a response (response rate = 21%). In addition, 11 non-International Society of Oncology Pharmacy Practitioners members also participated in the survey, bringing the total to 86 respondents. The top three areas in which respondents reported learning needs included evaluating comparative efficacy of a biosimilar to an originator's product (74.4%), managing the switchover to a biosimilar from the original product (74.4%), and understanding medication safety issues in relation to biosimilars use (73.3%). The most common challenges faced in obtaining education on biosimilars included limited financial support for education on biosimilar products (38.4%), heavy workload (31.4%), and inadequate educational resources (27.9%). Conclusion: This survey has identified numerous biosimilar learning needs as well as challenges faced in obtaining biosimilars education among oncology pharmacy practitioners. Educational activities should be created to address these learning needs, and innovative strategies should be considered to overcome practitioner's barriers in obtaining biosimilars education.